Enhanced photocatalytic activity of Cuprous Oxide nanoparticles for malachite green degradation under the visible light radiation. (6th January 2020) - Muthukumaran, M; Gnanamoorthy, G; Varun Prasath, P; Abinaya, M; Dhinagaran, G; Sagadevan, Suresh; Mohammad, Faruq; Oh, Won Chun; Venkatachalam, K
Abstract: Photocatalysis provides excellent potentials for the complete removal of organic pollutants in environmentally friendly ways and sustainable means of technology. It has been noted that under UV-visible light irradiation, nanostructured semiconductor metal oxides photocatalysts can degrade different organic pollutants. Taking into consideration of the photocatalytic activity, the present study deals with the synthesis of cuprous oxide (Cu2 O) nanoparticles (NPs) by the sonochemical method and characterized for their physicochemical, optical, and photocatalytic properties. The powdered X-ray diffraction (XRD) analysis confirmed for the cubic phase crystalline structure while the Field emission scanning electron microscopy (SEM) supported for the icosahedron morphology. The bandgap of the synthesized Cu2 O NPs was found to be 2.26 eV, which is the suitable bandgap energy so as to achieve the enhanced photocatalytic degradation efficiency. On testing for the degradation of Malachite green (MG) as a model pollutant, the synthesized Cu2 O NPs demonstrated a high degradation efficiency under visible light irradiation. The observed results suggest that the synthesized Cu2 O NPs are attractive photocatalysts for the degradation of toxic organic wastes in the water under visible light. Further investigation confirmed for the photocatalytic reduction of 4-nitrophenol (4-NP) into 4-aminophenol (4-AP) under aqueous conditions with visible light.